Sceletium tortuosum (L.) N.E. Br.: mesembrine alkaloid chemotype signatures in wild type, cultivated and in vitro tissues - Glyn-Woods, Christina (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.